The preparation of titanium dioxide deposited onto alumite and zic oxide catalyst for chlordane and 4-nitrophenol photodegradation - 320261 Chu, Chai Leng; Rusmidah Ali; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007